2019
DOI: 10.17705/1cais.04440
|View full text |Cite
|
Sign up to set email alerts
|

ICT-enabled Refugee Integration: A Research Agenda

Abstract: The recent phenomenon that has become known as the European refugee crisis is, in reality, a global problem. Accordingly, issues regarding refugee integration have become a central debate topic worldwide. In this paper, we examine how refugees use information and communication technology (ICT) in different regions across the world to understand how ICT supports their desperate journey to safety, their stay in temporary settlement camps, and their post-settlement inclusion in host countries. We conducted a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 46 publications
0
39
1
1
Order By: Relevance
“…From the very beginning, researchers have observed that this crisis is different from previous ones due to the significant reliance of refugees on technology, with the use of the Internet by refugees and asylum seekers reaching new records [2]. In response, IS studies have focused on the potential of Information and Communication Technologies (ICTs) in alleviating the ongoing humanitarian crisis [3].…”
Section: Introductionmentioning
confidence: 99%
“…From the very beginning, researchers have observed that this crisis is different from previous ones due to the significant reliance of refugees on technology, with the use of the Internet by refugees and asylum seekers reaching new records [2]. In response, IS studies have focused on the potential of Information and Communication Technologies (ICTs) in alleviating the ongoing humanitarian crisis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The field of IS has recently devoted much attention to issues of social inclusion of a variety of marginalized groups. For instance, IS researchers have examined how systems can be used to promote social inclusion of refugees [16,26,27] and people with disabilities [14,28,29,30]. A prominent theme in the IS social inclusion literature relates to gender diversity in the IT workforce [31,32,33].…”
Section: Social Inclusion and Emancipationmentioning
confidence: 99%
“…A significant portion of these numbers was considered digital literate youths worldwide [48]. As far as refugee populations are concerned, they seem to use mobile devices daily to face everyday difficulties [4,5,49,50]. The research revealed that most refugees own a mobile device, and more than 50% of young refugees use the Internet daily [19,50].…”
Section: Use Of Smart Mobile Devices By Refugeesmentioning
confidence: 99%
“…Upon the refugees' arrival in a host country, mobile devices constitute essential means for various uses. The ways refugees use mobile devices can be categorized into 12 categories based on the reviewed literature: (1) orientation, (2) accessibility to information, (3) availability of aid services for refugees, (4) availability of education and linguistic resources, (5) word/phrase translation in their native language, (6) admissibility to labor markets and entrepreneurship opportunities, (7) communication with loved ones in the home country, (8) socializing with the local population and other refugees in their host country, (9) money transfer, (10) interactivity with the host government, (11) volunteer coordination, and (12) self-help aid services [4,51,52].…”
Section: Use Of Smart Mobile Devices By Refugeesmentioning
confidence: 99%
See 1 more Smart Citation